2021
DOI: 10.1161/strokeaha.121.034778
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties and Controversies in the Management of Ischemic Stroke and Transient Ischemic Attack Patients With Patent Foramen Ovale

Abstract: Multiple randomized clinical trials have demonstrated the benefit of patent foramen ovale closure over medical therapy alone for patients who have had a stroke that has been attributed to the patent foramen ovale. Nevertheless, there are many areas of uncertainty and controversy related to patient selection, pathophysiology, diagnosis, and treatment. We summarize the available data on these challenging topics and attempt to provide some clarity and future directions for clinicians and investigators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 92 publications
(215 reference statements)
0
27
0
1
Order By: Relevance
“…Until 2017, the results of CLOSE [ 7 ], Gore REDUCE [ 8 ], and Long-Term Outcomes of RESPECT study [ 6 ] showed that PFO closure significantly reduced the recurrence rate of ischemic stroke in patients with CS. Multiple trial-level meta-analyses have confirmed the efficacy of closure, yielding an odds ratio (OR) of 0.44 compared with MT alone [ 9 , 22 24 ]. Subgroup analyses showed the benefit of PFO closure was significant in patients with PFO associated with substantial RLS or ASA [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until 2017, the results of CLOSE [ 7 ], Gore REDUCE [ 8 ], and Long-Term Outcomes of RESPECT study [ 6 ] showed that PFO closure significantly reduced the recurrence rate of ischemic stroke in patients with CS. Multiple trial-level meta-analyses have confirmed the efficacy of closure, yielding an odds ratio (OR) of 0.44 compared with MT alone [ 9 , 22 24 ]. Subgroup analyses showed the benefit of PFO closure was significant in patients with PFO associated with substantial RLS or ASA [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…New-onset AF is the commonest complication after PFO closure, with an incidence of 2.9%-6.6% [ 29 , 30 ]. AF mainly occurs within 30 days after the device implantation, possibly due to local inflammation after device implantation, irritation or stretching of the interatrial septum during device deployment, or the specific use of an umbrella-clamshell device [ 9 ]. As reported, 72% of new-onset AF recovered within 45 days spontaneously and would not increase the risk of ischemic stroke [ 1 , 7 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] Despite the clinical evidence for PFO closure in CS patients, many questions remain unanswered. 24 First, most previous trials were conducted in young patients (<60 years), and the benefit of PFO closure in elderly patients remains unknown. Although the greatest added benefit of PFO closure plus medical therapy compared with medical therapy alone was found in patients with both a high RoPE score and a high-risk PFO (socalled probable PASCAL), 8 this observation may in part be attributed to the fact that older patients were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Merke Da die Wirksamkeit des interventionellen PFO-Verschlusses bei kryptogenem Schlaganfall bei Patienten im Alter < 60 Jahre belegt ist, sollte diese Patientengruppe nicht mehr unter dem Label ESUS subsumiert werden [40,41]. Die neue Bezeichnung ist PFO-assoziierter Schlaganfall [41].…”
Section: Persistierendes Foramen Ovaleunclassified